Non‐invasive prenatal testing with cell‐free DNA: US physician attitudes toward implementation in clinical practice. (22nd March 2013) - Musci, Thomas J.; Fairbrother, Genevieve; Batey, Annette; Bruursema, Jennifer; Struble, Craig; Song, Ken
ABSTRACT Objective The aim of this study was to assess awareness, potential adoption, and current utilization of non‐invasive prenatal testing (NIPT) analysis for common fetal aneuploidies among obstetricians. Methods A 36‐item web‐based survey was designed to assess the current practice of fetal aneuploidy screening and knowledge and utilization of NIPT for fetal trisomy. Practicing obstetricians in the United States were invited via email to participate in the survey. Results Of the 101 obstetricians that completed the survey (27% academic‐based, 73% private practice), 97% offer screening to high‐risk patients and 91% offer screening to average‐risk patients. With regard to current screening tests, the top three advantages were as follows: recommendation by professional societies, no risk to the pregnancy, and long history/experience with the test, whereas the top three limitations were as follows: patient anxiety, risks of follow‐up invasive testing, and high false positives. NIPT had been used by 32% of respondents and 22% were familiar with NIPT and the associated clinical data. The majority of physicians predicted that they would offer NIPT to high‐risk women (86.1%) and average‐risk women (76.2%) within 12 months. Conclusion Obstetricians plan to increase their utilization of NIPT and expect that the majority of both high‐risk and average‐risk patients will be offered NIPT as an option. © 2013 John Wiley & Sons, Ltd.